Hand powered generator for low power applications - Kho, Anderson Ngap Chai. (2008)
This dissertation is a study on the various technical aspects of using human hand power to operate some of the ordinarily used applications. A prototype unit of a hand powered generator for low power applications is designed and built. Its potential as an alternative energy source is studied and examined, and presented in detail.